The degree of practicing inspirational leadership in Palestinian universities in Gaza governorates from the perspective of faculty members in light of the requirements of digital transformation (Palestine Technical College Journal for Research and Studies, 2023)
The study aimed to identify the degree of inspiring leadership practice in Palestinian universities in the governorates of Gaza from the point of view of its faculty members in light of the requirements of digital transformation, and using the descriptive approach, and reference to previous literature, a questionnaire was built that included (42) items distributed on (6) areas, namely (Self-confidence, strategic direction, transformation management, empowering and supporting employees, challenge and excellence, and dealing with failure) in light of the requirements of digital transformation. The results of the study showed that the degree of practicing inspirational leadership in Palestinian universities in the governorates of Gaza from the point of view of its faculty members in light of the requirements of digital transformation came to a large degree with a relative weight (77.73%), and there are no statistically significant differences in The degree of inspiring leadership practice in Palestinian universities in Gaza governorates from the point of view of their faculty members in light of the requirements of digital transformation due to the study variables (gender, academic qualification, number of years of service). Teaching in Palestinian universities.
Keywords: inspirational leadership; digital transformation; Palestinian universities